2018
DOI: 10.5483/bmbrep.2018.51.7.078
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide dismutase 3 protects mesenchymal stem cells through enhanced autophagy and regulation of FoxO3a trafficking

Abstract: Therapeutic applications of mesenchymal stem cells (MSCs) are limited due to their early death within the first few days of transplantation. Therefore, to improve the efficacy of cell-based therapies, it is necessary to manipulate MSCs so that they can resist various stresses imposed by the microenvironment. Moreover, the role of superoxide dismutase 3 (SOD3) in regulating such survival under different stress conditions remain elusive. In this study, we overexpressed SOD3 in MSCs (SOD3-MSCs) and evaluated its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Recently, it was observed that overexpression of SOD3 enhances the survival rate of UCB-MSCs under nutrientdeprived condition. Similarly, SOD3 attenuated starvation-induced apoptosis with reduced ROS levels under serum-starved condition [37]. Autophagy found to protect MSCs from oxidative stress-induced cell death.…”
Section: Sod3 In Msc Survival and Autophagymentioning
confidence: 86%
See 4 more Smart Citations
“…Recently, it was observed that overexpression of SOD3 enhances the survival rate of UCB-MSCs under nutrientdeprived condition. Similarly, SOD3 attenuated starvation-induced apoptosis with reduced ROS levels under serum-starved condition [37]. Autophagy found to protect MSCs from oxidative stress-induced cell death.…”
Section: Sod3 In Msc Survival and Autophagymentioning
confidence: 86%
“…However, SOD3 does not affect the expression levels of prostaglandin E2 and galectin-1 which are well known immunomodulatory regulators in MSCs [21]. Moreover, Overexpression of SOD3 was not found to regulate the cell size, complexity, and stemness of UCB-MSCs [37].…”
Section: Effects Of Sod3 In Msc Maintenance and Differentiationmentioning
confidence: 89%
See 3 more Smart Citations